Synthesis of oligomeric zinc complexes with bicyclic and acyclic guanidinate ligands - Neuhäuser, Christiane; Reinmuth, Matthias; Kaifer, Elisabeth; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2012)
Zinc dichloride and dimethylzinc were treated with several acyclic and bicyclic guanidines. Three different bicyclic guanidines and their potassium guanidinate salts were treated with ZnCl2. The reaction with the neutral guanidines afforded mononuclear complexes, stabilized by intramolecular hydrogen bonding. The reaction with the potassium guanidinate salts led to trinuclear complexes, which were extremely water sensitive. The reaction in the presence of added water furnished a tetranuclear complex with a central OZn4 unit in good yield, to which six guanidinate ligands were bound. The reaction of dimethylzinc with 2-[N,N′-diisopropylguanidino]pyridine and 2-[N,N′-diisopropylguanidino]quinoline afforded di- and tetranuclear Zn methyl complexes with mono- and dianionic guanidinate ligands. Dinuclear complexes of the monoanionic guanidinate ligands were formed at room temperature. At higher temperatures (75 °C), complete deprotonation of the guanidino groups and formation of tetranuclear Zn alkyl complexes was observed, which feature low-coordinate zinc sites.